Compensation for Factors of Production's Services under Uncertainty: Fixed Payment versus Profit-Loss Sharing Methods - Karim Eslamloueyan (جستارهای اقتصادی, 2022)
This article is an extension of the Eslamloueyan (2015). One of the key findings of that research is that the profit doesn't need to belong to only one production factor, but other inputs can also share in the profit. In addition, the economic principle that those who bear the risks are entitled to profit does not contradict Islamic viewpoints. Using a simple model, we compare the distribution system based on fixed payment to the profit-loss sharing system under uncertainty. Additionally, our framework allows us to examine Ayatollah Sadr's theory regarding the share of the Mamluk material owner in production. We argue that there is no difference between the fixed payments and the profit-loss sharing methods to compensate the services of production factors in the equilibrium under the certainty case. However, when there is uncertainty, our results suggest that replacing the fixed payment system with a profit-loss sharing system is more compatible with distributive justice and better maintains human dignity. Hence, to better compensate for the services of different factors of production, governments should take specific measures to promote a profit-loss-sharing system. Our findings might be used to develop a theory of profit for an economic system with an Islamic perspective.